2011
DOI: 10.1021/jf2024648
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Characteristics, and Stability of Glutathione-Loaded Nanoparticles

Abstract: The aim of this study was to investigate the characteristics and oxidative stability of chitosan-glutathione conjugate (CS-GSH) and CS-GSH nanoparticles (CS-GSH NPs) to explore the potentials of these nanoparticle systems for GSH delivery. CS-GSH was synthesized using a radical polymerization method, and CS-GSH NP was prepared by ionic gelation of CS-GSH with sodium tripolyphosphate (TPP). The sizes of CS-GSH NPs significantly increased with increasing CS-GSH concentration and CS-GSH/TPP ratio. The entrapment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Nanoparticles provide high capacity drug loading while maintaining resistance to enzymatic degradation, allowing prolonged drug delivery in the plasma with low toxicity side effects [226, 235]. One such nanoparticle, linking GSH and chitosan, maintains improved stability of GSH in oxidative conditions more effectively than free GSH [236]. Another type of nanoparticle used for drug-delivery across the BBB is dendrimers, a tree-like polymer, approximately 5nm in size, to which a number of functional groups can be attached [237].…”
Section: Gsh and Precursor Delivery As A Therapy For Parkinson’s Diseasementioning
confidence: 99%
“…Nanoparticles provide high capacity drug loading while maintaining resistance to enzymatic degradation, allowing prolonged drug delivery in the plasma with low toxicity side effects [226, 235]. One such nanoparticle, linking GSH and chitosan, maintains improved stability of GSH in oxidative conditions more effectively than free GSH [236]. Another type of nanoparticle used for drug-delivery across the BBB is dendrimers, a tree-like polymer, approximately 5nm in size, to which a number of functional groups can be attached [237].…”
Section: Gsh and Precursor Delivery As A Therapy For Parkinson’s Diseasementioning
confidence: 99%
“…Recent reports revealed that GSH was effective for the control of size and shape of Ag NPs. The surface modification of these colloidal nanoparticles is very important to facilitate their application to biotechnology and nanocomposites [19,20]. …”
Section: Introductionmentioning
confidence: 99%
“…Although it proved to be ineffective years ago [22], researchers continue to test the version [44], probably encouraged by the ability of apical membrane cells to uptake GSH [45]. Lipoceutical and transdermal vehicles as well as nanoparticles are also in testing phase [46,47]. There is at least one Lactobacillus strain under investigation with local (gastrointestinal) beneficial effects presumably due to its release of GSH [48].…”
Section: Discussionmentioning
confidence: 99%